PELATIHAN PEMANFAATAN GOOGLE CLASSROOM BAGI GURU DAN SISWA TPQ AL-AMIN SAWOJAJAR - Atika Syuliswati; Novi Nugrahani; Sri Hudiarini; Nurafni Eltifia; Atik Andhayani (Jurnal Pengabdian kepada Masyarakat, 2021)
This community service activity aims to share knowledge related to online learning methods which is currently needed during the pandemic by using online learning media as a support for improving educational services to teachers and students in the use of the Google Classroom application at the TPQ Al- Amin, which is located in Sawojajar inside Al-Furqan mosque. The method used is a practical and educative training method through lectures, simulations, and practices Google Classroom application which are carried out offline and online through Google meets, zoom, and Whatsapp class meetings. The training materials include classroom management, teachers, students, content, assignments, and grades. The result of this activity is the achievement of equal abilities in understanding and mastering the Google Classroom application for TPQ teachers and students as a supporter of online learning so that it can run effectively.